CONTRAST AND STIMULUS GENERALIZATION FOLLOWING PROLONGED DISCRIMINATION TRAINING1 - Hearst, Eliot (Journal of the experimental analysis of behavior, 1971)
Different groups of pigeons received discrimination training in which the reinforcement‐associated and extinction‐associated stimuli were respectively either (a) a line tilt vs a blank key, (b) a blank key vs a line tilt, or (c) two different line tilts. The high response rates that developed to the positive stimulus in all groups during discrimination learning were maintained over 64 sessions of training. After these sessions, all subjects were tested for stimulus generalization along the line‐tilt dimension. Gradients of relative (per cent) generalization around the stimulus associated with reinforcement (so‐called excitatory gradients) and around the stimulus associated with extinction (so‐called inhibitory gradients) were as steep as they typically are after much briefer training periods. These results do not support several of Terrace's predictions on the basis of the hypothesis that emotional responses develop to the stimulus associated with extinction during discrimination learning with errors, but eventually dissipate after extended training.